Evaluasi Pengalaman Pengguna Aplikasi Grab Driver menggunakan Metode UX Curve - Nurina Ayuningtyas; Hanifah Muslimah Az-Zahra; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Grab Driver is an application used by driver partners to do their jobs every day. In its effort to adapt the application to the needs of the driver partners, Grab made various updates to the application. Updates made to this application invite responses from users. This study then aims to identify the effect of these feature changes on user experience by evaluating long-term user experience using the UX Curve method. At the data collection stage, 100 curves were produced which were divided into 5 points of view, namely attractiveness, degree of usage, ease of use, and utility.. The results of data collection are 63 improving curves, 10 deteriorating curves, and also 27 stable curves. The total reason generated was 592 reasons with an average of 29.6 reasons per respondent (20.7 positive, and 8.9 negative N = 20). In all dimensions there is one feature that always gets positive comments namely the auto-accept feature. The existence of this feature has a positive impact on the Grab Driver application user experience. The most influential aspect of the Grab Driver application is the utility aspect with an average of 11.65 reasons stated by each user (7.45 positive and 4.2 negative, N = 20), and the least is the motivational aspect with an average of 5, 55 reasons (4.15 positive and 1.4 negative, N = 20). This indicates that to improve user experience, the most influential aspect is the utility aspect